Chrysin attenuates atopic dermatitis by suppressing inflammation of keratinocytes. (December 2017) - Choi, Jin Kyeong; Jang, Yong Hyun; Lee, Soyoung; Lee, Sang-Rae; Choi, Young-Ae; Jin, Meiling; Choi, Jung Ho; Park, Jee Hun; Park, Pil-Hoon; Choi, Hyukjae; Kwon, Taeg Kyu; Khang, Dongwoo; et al.
Abstract: We previously reported the inhibitory effect of chrysin, a natural flavonoid plentifully contained in propolis, vegetables and fruits, on the mast cell-mediated allergic reaction. In this study, we evaluated the effect of chrysin on atopic dermatitis (AD) and defined underlying mechanisms of action. We used an AD model in BALB/c mice by the repeated local exposure of 2, 4-dinitrochlorobenzene (DNCB) and house dust mite ( Dermatophagoides farinae extract, DFE) to the ears. Repeated alternative treatment of DNCB/DFE caused AD-like skin lesions. Oral administration of chrysin diminished AD symptoms such as ear thickness and histopathological analysis, in addition to serum IgE and IgG2a levels. Chrysin decreased infiltration of mast cells, and reduced serum histamine level. Chrysin also suppressed AD by inhibiting the inflammatory responses of Th1, Th2, and Th17 cells in mouse lymph node and ear. Interestingly, chrysin significantly inhibited the production of cytokines, Th2 chemokines, CCL17 and CCL22 by the down-regulation of p38 MAPK, NF-κB, and STAT1 in tumor necrosis factor (TNF)-α/interferon (IFN)-γ-stimulated human keratinocytes (HaCaT). Chrysin also inhibited TNF-α/IFN-γ-stimulated IL-33 expression in HaCaT cells and mouse primary keratinocytes. Taken together, the results indicate that chrysin suppressed AD symptoms, suggesting that chrysin might be a candidate for the treatment of AD and skin allergic diseases. Highlights: Chrysin suppresses AD symptoms by inhibiting T helper cell immune reaction. Chrysin downregulates CCL17 and CCL22 expression via p38 MAPK, STAT1, and NF-κB in human keratinocytes. Chrysin and tacrolimus have overlapping effects in inhibiting AD immune responses. Chrysin might be a candidate for the treatment of skin allergic diseases.